Isolation and purification of epithelial and endothelial cells from mouse lung - Nakano, Hideki (Methods Mol Biol, 2018)
Responses to inhaled environmental agents are controlled by the coordinated actions by multiple immune cell types, including macrophages, dendritic cells and lymphocytes. Recent evidence indicates that some structural cells can also contribute to the initiation and propagation of immune responses. For example, airway epithelial cells can promote eosinophilic inflammation in response to upon allergen inhalation. Much remains to be learned, however, regarding how each of these cell types interacts with the others, and how these interactions shape immune responses to inhaled agents. Such studies have been hampered by the lack of reliable methods to isolate multiple and distinct populations of cells from the same tissue sample. Consequently, investigators have had to choose between using different protocols with different animals to isolate different populations of cells, or accept that for some populations, cell yields are very low. To overcome these difficulties, we have developed a convenient and practical method to isolate and purify subpopulations of epithelial and endothelial cells from mouse lung. Here, we describe these methods in detail.